High-performance multifunctional silicone adhesive and preparation method thereof

CN122958984APending Publication Date: 2026-10-23GUANGXI HAORUI NANO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611333155.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但随着导热填料和阻燃填料用量增加,体系固体含量和界面数量明显增加,容易出现黏度升高、填料团聚、挤出困难以及固化性能波动等问题;特别是在单组分脱醇型室温硫化硅酮胶中,含羟基或易吸湿无机填料还可能带入吸附水,影响产品的储存稳定性

Benefits of technology

[0021]本发明以六方氮化硼为导热骨架,通过异丙醇铝受控水解及水热处理,在其表面构建具有特点覆盖程度的非连续勃姆石纳米域,使阻燃功能区域与氮化硼裸露导热区域共存,从而避免连续无机包覆层过度遮蔽氮化硼颗粒之间的有效接触界面,在提高阻燃性能的同时保持较完整的热传递通路。进一步地,在非连续勃姆石纳米域形成后采用限量辛基三乙氧基硅烷进行表面处理,可降低勃姆石富羟基表面引起的颗粒间作用、吸湿及团聚倾向,改善复合填料在聚硅氧烷体系中的分散状态和加工流动性,并减小吸附水对单组分脱醇型硅酮胶储存过程中交联体系稳定性的影响。由此,本发明通过对勃姆石纳米域的形成位置、覆盖程度以及后续疏水化程度进行连续调控,使导热、阻燃、施工性和储存稳定性之间形成相互协调的性能关系,克服了单纯增加阻燃相易损害导热和施工性能、单纯提高疏水处理程度又可能增加有机界面热阻的矛盾,实现了多项性能的综合平衡。因此,本发明的技术效果来源于非连续阻燃纳米域与受控界面疏水化之间的协同作用,而非各功能组分已知作用的简单叠加,具有较好的导热阻燃综合性能、挤出施工性能及储存稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958984A_ABST
    Figure CN122958984A_ABST
Patent Text Reader

Abstract

The application discloses a high-performance multifunctional silicone adhesive and a preparation method thereof, and belongs to the technical field of organic silicon materials. The method comprises the following steps: surface activation is performed on hexagonal boron nitride; isopropyl alcohol aluminum is controlled to be hydrolyzed and is subjected to hydrothermal treatment, so that non-continuous boehmite nano domains are formed on the surface of the hexagonal boron nitride; the boehmite nano domains correspond to an aluminum element enrichment area, and the aluminum element enrichment area accounts for 15-45% of the projected area of the surface of the hexagonal boron nitride particles; then limited surface treatment is performed on the boehmite nano domain modified boron nitride by using octyl triethoxysilane, so that a hydrophobic boehmite nano domain modified boron nitride is obtained; the boehmite nano domain modified boron nitride is mixed with alkoxyl-terminated polydimethylsiloxane, spherical alumina, dimethyl silicone oil and hydrophobic fumed silicon dioxide, vacuum dehydration and mixing are performed, and then a crosslinking agent, a silane coupling agent and an organic titanium catalyst are added, so that a single-component dealcoholized silicone adhesive is obtained. The application can play a flame-retardant role while maintaining effective heat conduction contact of the boron nitride, and construction performance and storage stability are also considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organosilicon materials technology, and in particular to a high-performance multifunctional silicone sealant and its preparation method. Background Technology

[0002] Silicone sealants are widely used for bonding, sealing, and potting in electronics, electrical appliances, power batteries, communication devices, and industrial equipment due to their excellent weather resistance, electrical insulation properties, high and low temperature resistance, and good flexibility. With the development of electronic devices towards higher power density and miniaturization, silicone sealants, in addition to their basic bonding and sealing performance, also need to possess high thermal conductivity, flame retardancy, workability, and storage stability. Currently, common techniques mainly involve adding thermally conductive fillers such as alumina, boron nitride, and aluminum nitride to polysiloxane systems, and compounding them with aluminum hydroxide, boehmite, or phosphorus-nitrogen-based flame retardant components to achieve both thermal conductivity and flame retardancy. To improve the compatibility between the numerous inorganic fillers and the organosilicon matrix, silane coupling agents or other surface treatment agents are often used to modify the fillers. However, with the increase in the amount of thermally conductive and flame-retardant fillers, the solid content and number of interfaces in the system increase significantly, which can easily lead to problems such as increased viscosity, filler agglomeration, extrusion difficulties, and fluctuations in curing performance. In particular, in single-component de-alcoholized room temperature vulcanizing silicone sealants, hydroxyl-containing or hygroscopic inorganic fillers may also introduce adsorbed water, affecting the storage stability of the product.

[0003] In existing technologies, while directly compounding thermally conductive and flame-retardant fillers can provide thermal conductivity and flame retardancy respectively, both types of fillers often require high dosages, making it difficult to balance the continuity of the thermal conductivity pathway with workability. Further forming a continuous oxide or hydroxide coating layer on the surface of high thermal conductivity fillers such as boron nitride may obscure the effective contact interface between thermally conductive particles, increasing interfacial thermal resistance. On the other hand, aluminum-based flame-retardant materials such as boehmite contain many polar hydroxyl groups on their surface, which, while beneficial for forming an inorganic flame-retardant barrier, can also easily lead to enhanced interparticle hydrogen bonding, increased hygroscopicity, and system thickening. Using a high dosage of organosilane for overall hydrophobic coating may form an excessively thick organic interfacial layer on the surface of the thermally conductive particles, hindering heat transfer. Therefore, existing technologies still lack a solution that can rationally configure flame-retardant functional areas on the surface of thermally conductive fillers while simultaneously controlling their coverage and interfacial hydrophobicity to improve flame-retardant performance without excessively disrupting the effective thermal contact of boron nitride, while also considering the dispersibility, workability, and storage stability of single-component de-alcoholized silicone sealants. Summary of the Invention

[0004] To address the aforementioned problems, this invention proposes a high-performance multifunctional silicone sealant and its preparation method. By surface activation of hexagonal boron nitride, followed by controlled hydrolysis and hydrothermal treatment with aluminum isopropoxide, discontinuous boehmite nanodomains are constructed on its surface. These nanodomains are then introduced into a one-component de-alcoholized silicone sealant system after limited hydrophobic treatment with octyltriethoxysilane. By controlling the coverage of the flame-retardant nanodomains and the degree of interface hydrophobicity, the flame retardancy, dispersibility, workability, and storage stability of the material are improved while retaining the effective thermally conductive contact of boron nitride.

[0005] This invention can be achieved through the following technical solutions:

[0006] A method for preparing a high-performance multifunctional silicone sealant includes the following steps:

[0007] S1. Hexagonal boron nitride is dispersed in an aqueous hydrogen peroxide solution for surface activation treatment. After solid-liquid separation, washing and drying, surface-activated boron nitride is obtained.

[0008] S2. Surface-activated boron nitride is dispersed in an alcohol dispersion medium. 18–36 parts by weight of aluminum isopropoxide are added per 100 parts by weight of surface-activated boron nitride, and water is added for controlled hydrolysis, allowing the aluminum hydrolysis products to nucleate on the surface of the surface-activated boron nitride. The ratio of water to aluminum isopropoxide is (2.1–2.8) mol: 1 mol. Subsequently, hydrothermal treatment is performed, followed by solid-liquid separation and washing to obtain a boron nitride composite filler with discontinuous boehmite nanodomains on its surface. The aluminum enrichment region corresponding to the boehmite nanodomains accounts for 15–45% of the projected surface area of ​​the hexagonal boron nitride particles. 0.8–2.0 parts by weight of octyltriethoxysilane are added per 100 parts by weight of the boron nitride composite filler for surface treatment, followed by drying to obtain hydrophobic boehmite nanodomain-modified boron nitride.

[0009] S3. Alkoxy-terminated polydimethylsiloxane, hydrophobic boehmite nanodomain modified boron nitride, spherical alumina, dimethyl silicone oil and hydrophobic fumed silica are mixed and then vacuum dehydrated and kneaded to obtain an anhydrous base material.

[0010] S4. Add alkoxysilane crosslinking agent, silane coupling agent and organotitanium catalyst to anhydrous base material, and then vacuum mix and degas to obtain high-performance multifunctional silicone sealant.

[0011] Preferably, the average particle size of the hexagonal boron nitride is 5–20 μm, and the mass concentration of the hydrogen peroxide aqueous solution is 10–20%.

[0012] Preferably, the surface activation treatment temperature in S1 is 60-80°C, and the treatment time is 2-6 h.

[0013] Preferably, in step S2, the controlled hydrolysis temperature is 50–70°C and the controlled hydrolysis time is 1–3 h; the hydrothermal treatment temperature is 120–160°C and the hydrothermal treatment time is 2–5 h.

[0014] Preferably, the average equivalent particle size of the boehmite nanodomains in S2 is 30–150 nm, and the boehmite nanodomains are discretely distributed on the hexagonal boron nitride surface; the surface projection area ratio of the aluminum enrichment region is statistically determined by scanning electron microscopy combined with energy dispersive spectroscopy elemental surface distribution.

[0015] Preferably, the surface treatment temperature of octyltriethoxysilane in S2 is 60-80°C and the treatment time is 2-4 h; after surface treatment, vacuum drying is performed so that the moisture content of the obtained hydrophobic boehmite nanodomain modified boron nitride is not higher than 0.15 wt%.

[0016] Preferably, in S3, based on 100 parts by weight of alkoxy-terminated polydimethylsiloxane, the hydrophobic boehmite nanodomain modified boron nitride comprises 50-90 parts by weight, the spherical alumina comprises 120-220 parts by weight, the dimethyl silicone oil comprises 8-18 parts by weight, and the hydrophobic fumed silica comprises 1-4 parts by weight.

[0017] Preferably, in step S3, the vacuum dehydration mixing temperature is 100-120℃, the vacuum degree is -0.090--0.098MPa, and the dehydration mixing time is 1-2 h; after the dehydration mixing is completed, the anhydrous base material is cooled to no higher than 40℃.

[0018] Preferably, in S4, based on 100 parts by weight of alkoxy-terminated polydimethylsiloxane, the alkoxysilane crosslinking agent includes 3-6 parts by weight of methyltrimethoxysilane and 1-3 parts by weight of vinyltrimethoxysilane; the silane coupling agent is γ-glycidoxypropyltrimethoxysilane, added in an amount of 0.5-1.5 parts by weight; and the organotitanium catalyst is diisopropyl bis(ethyl acetoacetate) titanate, added in an amount of 0.2-0.8 parts by weight.

[0019] The high-performance multifunctional silicone sealant prepared by this invention is a single-component de-alcoholized room temperature vulcanizing silicone sealant, wherein the surface of hexagonal boron nitride is distributed with discontinuous boehmite nanodomains that have been surface-treated with octyltriethoxysilane.

[0020] The beneficial effects of this invention are:

[0021] This invention uses hexagonal boron nitride as a thermally conductive framework. Through controlled hydrolysis and hydrothermal treatment of aluminum isopropoxide, discontinuous boehmite nanodomains with a specific coverage are constructed on its surface. This allows the flame-retardant functional area to coexist with the exposed thermally conductive boron nitride area, thereby avoiding excessive obscuring of the effective contact interface between boron nitride particles by the continuous inorganic coating layer. This improves flame retardancy while maintaining a relatively complete heat transfer pathway. Furthermore, after the formation of the discontinuous boehmite nanodomains, a limited amount of octyltriethoxysilane is used for surface treatment, which reduces interparticle interactions, moisture absorption, and agglomeration tendency caused by the hydroxyl-rich surface of the boehmite. This improves the dispersion and processing fluidity of the composite filler in the polysiloxane system and reduces the impact of adsorbed water on the stability of the crosslinking system during the storage of single-component de-alcoholized silicone sealant. Therefore, this invention achieves a coordinated performance relationship between thermal conductivity, flame retardancy, workability, and storage stability by continuously controlling the formation location, coverage, and subsequent hydrophobicity of boehmite nanodomains. This overcomes the contradiction that simply increasing the flame retardant phase can easily damage thermal conductivity and workability, while simply increasing the degree of hydrophobic treatment may increase the thermal resistance of the organic interface, thus achieving a comprehensive balance of multiple properties. Therefore, the technical effect of this invention stems from the synergistic effect between discontinuous flame retardant nanodomains and controlled interface hydrophobicity, rather than a simple superposition of the known effects of each functional component, resulting in better overall thermal conductivity and flame retardancy, extrusion workability, and storage stability. Attached Figure Description

[0022] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings:

[0023] Figure 1 This is a schematic diagram of the preparation process of silicone sealant. Detailed Implementation

[0024] The following provides a detailed description of the embodiments of the present invention: These embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation methods and processes. However, the scope of protection of the present invention is not limited to the following embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions.

[0025] Example 1: A method for preparing a high-performance multifunctional silicone sealant, comprising the following steps:

[0026] S1. Take 100 parts of hexagonal boron nitride with an average particle size of 5 μm, add it to 500 parts of hydrogen peroxide aqueous solution with a mass concentration of 10%, stir and disperse, treat at 60℃ for 2 h, filter, wash with deionized water until the filtrate is neutral, dry, and obtain surface activated boron nitride.

[0027] S2. 100 parts of surface-activated boron nitride were dispersed in 500 parts of isopropanol, 18 parts of aluminum isopropoxide were added, and then 3.33 parts of water were added to make the molar ratio of water to aluminum in aluminum isopropoxide 2.1:1. The mixture was reacted at 50℃ for 1 h. Then it was transferred to a hydrothermal reactor and treated at 120℃ for 2 h. After filtration and washing, a boron nitride composite filler with discontinuous boehmite nanodomains on the surface was obtained. SEM-EDS analysis showed that the average equivalent particle size of the obtained boehmite nanodomains was about 30 nm, and the aluminum enrichment region accounted for about 15% of the surface projection area of ​​the hexagonal boron nitride particles. 100 parts of the above boron nitride composite filler were taken, 0.8 parts of octyltriethoxysilane were added, and the mixture was treated at 60℃ for 2 h. Then it was vacuum dried at 110℃ and -0.095 MPa. The water content of the hydrophobic boehmite nanodomain modified boron nitride was 0.15 wt%.

[0028] S3. Take 100 parts of alkoxy-terminated polydimethylsiloxane, 50 parts of hydrophobic boehmite nanodomain modified boron nitride, 120 parts of spherical alumina, 8 parts of dimethyl silicone oil and 1 part of hydrophobic fumed silica and add them to a vacuum planetary mixer and mix. Dehydrate and knead for 1 h at 100℃ and -0.090 MPa. After completion, cool to 40℃ to obtain anhydrous base material.

[0029] S4. Under dry conditions, add 3 parts of methyltrimethoxysilane, 1 part of vinyltrimethoxysilane, 0.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane and 0.2 parts of diisopropyl bis(ethyl acetoacetate) titanate to the above anhydrous base material, vacuum mix and degas, then seal and package to obtain high-performance multifunctional silicone sealant.

[0030] Example 2: A method for preparing a high-performance multifunctional silicone sealant, comprising the following steps:

[0031] S1. Take 100 parts of hexagonal boron nitride with an average particle size of 20 μm, add it to 500 parts of hydrogen peroxide aqueous solution with a mass concentration of 20%, stir and disperse, treat at 80℃ for 6 h, filter, wash with deionized water until the filtrate is neutral, dry, and obtain surface-activated boron nitride.

[0032] S2. 100 parts of surface-activated boron nitride were dispersed in 500 parts of isopropanol, 36 parts of aluminum isopropoxide were added, and then 8.89 parts of water were added to make the molar ratio of water to aluminum in aluminum isopropoxide 2.8:1. The mixture was reacted at 70℃ for 3 h. Then it was transferred to a hydrothermal reactor and treated at 160℃ for 5 h. After filtration and washing, a boron nitride composite filler with discontinuous boehmite nanodomains on the surface was obtained. SEM-EDS analysis showed that the average equivalent particle size of the obtained boehmite nanodomains was about 150 nm, and the aluminum enrichment area accounted for about 45% of the surface projection area of ​​the hexagonal boron nitride particles. 100 parts of the above boron nitride composite filler were taken, 2.0 parts of octyltriethoxysilane were added, and the mixture was treated at 80℃ for 4 h. Then it was vacuum dried at 110℃ and -0.095 MPa. The water content of the hydrophobic boehmite nanodomain modified boron nitride was 0.10 wt%.

[0033] S3. Take 100 parts of alkoxy-terminated polydimethylsiloxane, 90 parts of hydrophobic boehmite nanodomain modified boron nitride, 220 parts of spherical alumina, 18 parts of dimethyl silicone oil and 4 parts of hydrophobic fumed silica and add them to a vacuum planetary mixer and mix. Dehydrate and knead at 120℃ and -0.098 MPa for 2 h. After completion, cool to 35℃ to obtain anhydrous base material.

[0034] S4. Under dry conditions, add 6 parts of methyltrimethoxysilane, 3 parts of vinyltrimethoxysilane, 1.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane and 0.8 parts of diisopropyl bis(ethyl acetoacetate) titanate to the above anhydrous base material. After vacuum mixing and degassing, seal and package to obtain high-performance multifunctional silicone sealant.

[0035] Example 3: A method for preparing a high-performance multifunctional silicone sealant, comprising the following steps:

[0036] S1. Take 100 parts of hexagonal boron nitride with an average particle size of 12 μm, add it to 500 parts of hydrogen peroxide aqueous solution with a mass concentration of 15%, stir and disperse, treat at 70℃ for 4 h, filter, wash with deionized water until the filtrate is neutral, dry, and obtain surface activated boron nitride.

[0037] S2. 100 parts of surface-activated boron nitride were dispersed in 500 parts of isopropanol, 27 parts of aluminum isopropoxide were added, and then 5.83 parts of water were added to make the molar ratio of water to aluminum in aluminum isopropoxide 2.45:1. The mixture was reacted at 60℃ for 2 h. Then it was transferred to a hydrothermal reactor and treated at 140℃ for 3.5 h. After filtration and washing, a boron nitride composite filler with discontinuous boehmite nanodomains on the surface was obtained. SEM-EDS analysis showed that the average equivalent particle size of the obtained boehmite nanodomains was about 90 nm, and the aluminum enrichment area accounted for about 30% of the surface projection area of ​​the hexagonal boron nitride particles. 100 parts of the above boron nitride composite filler were taken, 1.4 parts of octyltriethoxysilane were added, and the mixture was treated at 70℃ for 3 h. Then it was vacuum dried at 110℃ and -0.095 MPa. The water content of the hydrophobic boehmite nanodomain modified boron nitride was 0.12 wt%.

[0038] S3. Take 100 parts of alkoxy-terminated polydimethylsiloxane, 70 parts of hydrophobic boehmite nanodomain modified boron nitride, 170 parts of spherical alumina, 13 parts of dimethyl silicone oil and 2.5 parts of hydrophobic fumed silica and add them to a vacuum planetary mixer and mix. Dehydrate and knead for 1.5 h at 110℃ and -0.094 MPa. After completion, cool to 35℃ to obtain anhydrous base material.

[0039] S4. Under dry conditions, add 4.5 parts of methyltrimethoxysilane, 2 parts of vinyltrimethoxysilane, 1.0 part of γ-glycidyl etheroxypropyltrimethoxysilane and 0.5 parts of diisopropyl bis(ethyl acetoacetate) titanate to the above anhydrous base material, vacuum mix and degas, then seal and package to obtain high-performance multifunctional silicone sealant.

[0040] Comparative Example 1: The difference between this comparative example and Example 1 is that instead of using controlled hydrolysis of aluminum isopropoxide and hydrothermal treatment to form boehmite nanodomains in situ on the surface of hexagonal boron nitride, hexagonal boron nitride and an equal amount of boehmite are directly physically mixed and then subjected to octyltriethoxysilane surface treatment.

[0041] The preparation method of the silicone sealant in this comparative example includes the following steps:

[0042] S1. Take 100 parts of hexagonal boron nitride with an average particle size of 5 μm, add it to 500 parts of hydrogen peroxide aqueous solution with a mass concentration of 10%, stir and disperse, treat at 60℃ for 2 h, filter, wash with deionized water until the filtrate is neutral, dry, and obtain surface activated boron nitride.

[0043] S2. Take 100 parts of surface-activated boron nitride, add 5.3 parts of boehmite with an average particle size of 30 nm, mix evenly to obtain boron nitride-boehmite physical mixed filler; take 100 parts of the boron nitride-boehmite physical mixed filler, add 0.8 parts of octyltriethoxysilane, treat at 60℃ for 2 h, and then vacuum dry at 110℃ and -0.095 MPa to obtain hydrophobic boron nitride-boehmite physical mixed filler;

[0044] S3. Take 100 parts of alkoxy-terminated polydimethylsiloxane, 50 parts of hydrophobically treated boron nitride-boehmite physical mixed filler, 120 parts of spherical alumina, 8 parts of dimethyl silicone oil and 1 part of hydrophobic fumed silica and add them to a vacuum planetary mixer and mix. Dehydrate and knead for 1 h at 100℃ and -0.090 MPa. After completion, cool to 40℃ to obtain anhydrous base material.

[0045] S4. Under dry conditions, add 3 parts of methyltrimethoxysilane, 1 part of vinyltrimethoxysilane, 0.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane and 0.2 parts of diisopropyl bis(ethyl acetoacetate) titanate to the above anhydrous base material, vacuum mix and degas, then seal and package to obtain silicone sealant.

[0046] Comparative Example 2: The difference between this comparative example and Example 1 is that the amount of aluminum isopropoxide and water added is increased, so that the projected area of ​​the aluminum enrichment region on the surface of the boehmite reaches about 65%, forming a high-coverage boehmite coating structure.

[0047] The preparation method of the silicone sealant in this comparative example includes the following steps:

[0048] S1. Take 100 parts of hexagonal boron nitride with an average particle size of 5 μm, add it to 500 parts of hydrogen peroxide aqueous solution with a mass concentration of 10%, stir and disperse, treat at 60℃ for 2 h, filter, wash with deionized water until the filtrate is neutral, dry, and obtain surface activated boron nitride.

[0049] S2. Take 100 parts of surface-activated boron nitride and disperse it in 500 parts of isopropanol. Add 54 parts of aluminum isopropoxide and then add 10.00 parts of water to keep the molar ratio of water to aluminum in aluminum isopropoxide at 2.1:1. React at 50℃ for 1 h. Then transfer it to a hydrothermal reactor and treat it at 120℃ for 2 h. Filter and wash to obtain boron nitride with high coverage. According to SEM-EDS analysis, the aluminum enrichment area accounts for about 65% of the surface projection area of ​​the hexagonal boron nitride particles. Take 100 parts of the above boron nitride with high coverage and add 0.8 parts of octyltriethoxysilane. Treat it at 60℃ for 2 h and then vacuum dry it at 110℃ and -0.095 MPa.

[0050] S3. Take 100 parts of alkoxy-terminated polydimethylsiloxane, 50 parts of high-coverage boehmite-modified boron nitride, 120 parts of spherical alumina, 8 parts of dimethyl silicone oil and 1 part of hydrophobic fumed silica and add them to a vacuum planetary mixer and mix. Dehydrate and knead for 1 h at 100℃ and -0.090 MPa. After completion, cool to 40℃ to obtain anhydrous base material.

[0051] S4. Under dry conditions, add 3 parts of methyltrimethoxysilane, 1 part of vinyltrimethoxysilane, 0.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane and 0.2 parts of diisopropyl bis(ethyl acetoacetate) titanate to the above anhydrous base material, vacuum mix and degas, then seal and package to obtain silicone sealant.

[0052] Comparative Example 3: The difference between this comparative example and Example 1 is that after forming the discontinuous boehmite nanodomains, octyltriethoxysilane is not added for surface treatment. Instead, the obtained boehmite nanodomains are directly modified with boron nitride, dried, and then used for the preparation of silicone sealant.

[0053] The preparation method of the silicone sealant in this comparative example includes the following steps:

[0054] S1. Take 100 parts of hexagonal boron nitride with an average particle size of 5 μm, add it to 500 parts of hydrogen peroxide aqueous solution with a mass concentration of 10%, stir and disperse, treat at 60℃ for 2 h, filter, wash with deionized water until the filtrate is neutral, dry, and obtain surface activated boron nitride.

[0055] S2. 100 parts of surface-activated boron nitride were dispersed in 500 parts of isopropanol, 18 parts of aluminum isopropoxide were added, and then 3.33 parts of water were added to make the molar ratio of water to aluminum in aluminum isopropoxide 2.1:1. The mixture was reacted at 50℃ for 1 h. Then it was transferred to a hydrothermal reactor and treated at 120℃ for 2 h. After filtration and washing, a boron nitride composite filler with discontinuous boehmite nanodomains on the surface was obtained. According to SEM-EDS analysis, the average equivalent particle size of the obtained boehmite nanodomains was about 30 nm, and the aluminum enrichment area accounted for about 15% of the surface projection area of ​​the hexagonal boron nitride particles. The obtained boron nitride composite filler was not subjected to octyltriethoxysilane surface treatment, but was directly vacuum dried at 110℃ and -0.095 MPa to obtain boron nitride modified with boehmite nanodomains without hydrophobic treatment.

[0056] S3. Take 100 parts of alkoxy-terminated polydimethylsiloxane, 50 parts of boehmite nanodomain modified boron nitride without hydrophobic treatment, 120 parts of spherical alumina, 8 parts of dimethyl silicone oil and 1 part of hydrophobic fumed silica and add them to a vacuum planetary mixer and mix. Dehydrate and knead for 1 h at 100℃ and -0.090 MPa. After completion, cool to 40℃ to obtain anhydrous base material.

[0057] S4. Under dry conditions, add 3 parts of methyltrimethoxysilane, 1 part of vinyltrimethoxysilane, 0.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane and 0.2 parts of diisopropyl bis(ethyl acetoacetate) titanate to the above anhydrous base material, vacuum mix and degas, then seal and package to obtain silicone sealant.

[0058] Performance testing

[0059] 1. Thermal conductivity

[0060] Each group of silicone sealant was injected into a mold and allowed to fully cure at a temperature of 23±2℃ and a relative humidity of 50±5% to prepare sheet-like samples with a thickness of 2.0 mm. The thermal conductivity of the samples was tested using the transient planar heat source method at a test temperature of 25℃.

[0061] 2. Flame retardant properties

[0062] Each group of silicone sealants was prepared into strip-shaped samples with a length of 125 mm, a width of 13 mm, and a thickness of 2.0 mm. After being fully cured at 23±2℃ and a relative humidity of 50±5%, a vertical combustion test was conducted.

[0063] Record the flaming time of the sample after the first and second flaming, whether molten droplets occur, and whether the cotton pad below is ignited, and determine its vertical flaming rating based on the test results.

[0064] 3. Extrusion performance

[0065] After each group of uncured silicone sealant was placed at 23±2℃ for 24 h, it was put into a sealing tube of the same specification. Using a standard dispensing nozzle with an inner diameter of 3 mm, it was continuously extruded for 60 s under a constant air pressure of 0.03 MPa. The extruded silicone sealant was collected and weighed.

[0066] The extrusion ratio is calculated using the following formula:

[0067] Extrusion rate = mass of silicone sealant extruded within 60 s / 60 s.

[0068] 4. Thermal storage stability

[0069] Each group of uncured silicone sealant was sealed in an aluminum-plastic composite tube of the same specification and stored at a constant temperature of 50℃ for 28 days. After being removed, it was placed at 23±2℃ for 24 hours. The extrusion rate was measured before and after storage according to the above extrusion performance test method, and the extrusion rate retention rate was calculated according to the following formula:

[0070] Extrusion rate retention rate = Extrusion rate after heat storage / Extrusion rate before heat storage × 100%.

[0071] Simultaneously, the surface drying time before and after heat storage was measured. An appropriate amount of silicone sealant was used to make a layer with a thickness of about 2 mm. The layer was placed in an environment with a temperature of 23±2℃ and a relative humidity of 50±%. Every certain period of time, the surface of the sealant layer was lightly touched with a polyethylene film. The time when the film could be peeled off and there was no obvious adhesive on the surface was taken as the surface drying time.

[0072] Table 1. Test results of various properties of silicone sealant

[0073] Example 1 1.62 V-0 126 116 92.1 18 20 Example 2 2.36 V-0 76 68 8.5 21 24 Example 3 1.98 V-0 101 95 94.1 19 21 Comparative Example 1 1.39 V-1 88 68 77.3 19 30 Comparative Example 2 1.25 V-0 61 45 73.8 21 34 Comparative Example 3 1.47 V-0 72 43 59.7 20 46

[0074] As shown in Table 1, the silicone sealants prepared by this invention all achieve a V-0 flame retardant rating, with a thermal conductivity of 1.62–2.36 W / (m·K). The extrusion yield retention rate after thermal storage is 89.5%–94.1%, and the surface drying time before and after storage changes little, demonstrating excellent comprehensive performance in terms of thermal conductivity, flame retardancy, application, and storage. These results indicate that by controlling the hydrolysis of aluminum isopropoxide to form 15–45% discontinuous boehmite nanodomains on the surface of hexagonal boron nitride, followed by limited octyltriethoxysilane surface treatment, it is possible to avoid the formation of a continuous boehmite coating that excessively hinders effective heat transfer between boron nitride particles. Simultaneously, the locally distributed boehmite nanodomains impart flame retardancy. Further limited hydrophobic treatment reduces the adverse effects of the surface polarity and hygroscopicity of the boehmite on filler dispersion and the storage stability of the single-component de-alcoholization system. Examples 1-3 all maintained good overall performance, indicating that the effect obtained by the present invention is not a simple superposition of the functions of the thermally conductive filler, flame retardant component and silane treatment, but a balance of thermal conductivity, flame retardancy, construction and storage performance formed by the controlled spatial distribution of discontinuous nanodomains and subsequent interface hydrophobic regulation.

[0075] Compared to Example 1, Comparative Example 1, which replaced the in-situ formed discontinuous boehmite nanodomains with a direct physical mixture of hexagonal boron nitride and boehmite, saw its thermal conductivity decrease to 1.39 W / (m·K), flame retardancy rating drop to V⁻¹, and extrusion rate retention decrease to 77.3%. This demonstrates that simple blending is insufficient to form a stable and effective thermally conductive / flame-retardant interface structure and cannot replace the in-situ nanodomain construction method of this invention. Comparative Example 2, by increasing the boehmite coverage to approximately 65%, saw its thermal conductivity decrease to 1.25 W / (m·K), and its initial extrusion rate and post-heat storage extrusion rate retention decreased to 61 g / min and 73.8%, respectively. This indicates that excessive boehmite coverage can obscure the effective thermally conductive contact area of ​​boron nitride and enhance interfacial interactions between fillers, proving that more boehmite coverage is not necessarily more beneficial. In Comparative Example 3, after the removal of octyltriethoxysilane treatment, the initial extrusion rate decreased to 72 g / min, the extrusion rate retention rate after heat storage further decreased to 59.7%, and the surface drying time was extended to 46 min. This indicates that the main function of the limited octylsilane treatment is not simply to increase thermal conductivity or flame retardancy, but to regulate the interfacial polarity, moisture absorption and agglomeration problems caused by the introduction of boehmite nanodomains.

[0076] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing a high-performance multifunctional silicone sealant, characterized in that, Includes the following steps: S1. Hexagonal boron nitride is dispersed in an aqueous hydrogen peroxide solution for surface activation treatment. After solid-liquid separation, washing and drying, surface-activated boron nitride is obtained. S2. Surface-activated boron nitride is dispersed in an alcohol dispersion medium. 18–36 parts by weight of aluminum isopropoxide are added per 100 parts by weight of surface-activated boron nitride, and water is added for controlled hydrolysis, allowing the aluminum hydrolysis products to nucleate on the surface of the surface-activated boron nitride. The ratio of water to aluminum isopropoxide is (2.1–2.8) mol: 1 mol. Subsequently, hydrothermal treatment is performed, followed by solid-liquid separation and washing to obtain a boron nitride composite filler with discontinuous boehmite nanodomains on its surface. The aluminum enrichment region corresponding to the boehmite nanodomains accounts for 15–45% of the projected surface area of ​​the hexagonal boron nitride particles. 0.8–2.0 parts by weight of octyltriethoxysilane are added per 100 parts by weight of the boron nitride composite filler for surface treatment, followed by drying to obtain hydrophobic boehmite nanodomain-modified boron nitride. S3. Alkoxy-terminated polydimethylsiloxane, hydrophobic boehmite nanodomain modified boron nitride, spherical alumina, dimethyl silicone oil and hydrophobic fumed silica are mixed and then vacuum dehydrated and kneaded to obtain an anhydrous base material. S4. Add alkoxysilane crosslinking agent, silane coupling agent and organotitanium catalyst to anhydrous base material, and then vacuum mix and degas to obtain high-performance multifunctional silicone sealant.

2. The method for preparing the high-performance multifunctional silicone sealant according to claim 1, characterized in that, The average particle size of the hexagonal boron nitride is 5–20 μm, and the mass concentration of the hydrogen peroxide aqueous solution is 10–20%.

3. The method for preparing high-performance multifunctional silicone sealant according to claim 1, characterized in that, The surface activation treatment temperature in S1 is 60–80°C, and the treatment time is 2–6 h.

4. The method for preparing the high-performance multifunctional silicone sealant according to claim 1, characterized in that, In S2, the controlled hydrolysis temperature is 50–70°C and the controlled hydrolysis time is 1–3 h; the hydrothermal treatment temperature is 120–160°C and the hydrothermal treatment time is 2–5 h.

5. The method for preparing the high-performance multifunctional silicone sealant according to claim 1, characterized in that, The average equivalent particle size of the boehmite nanodomains in S2 is 30–150 nm, and the boehmite nanodomains are discretely distributed on the hexagonal boron nitride surface. The surface projection area ratio of the aluminum enrichment region is statistically determined by scanning electron microscopy combined with energy dispersive spectroscopy.

6. The method for preparing the high-performance multifunctional silicone sealant according to claim 1, characterized in that, The surface treatment temperature of octyltriethoxysilane in S2 is 60-80℃, and the treatment time is 2-4 h. After surface treatment, vacuum drying is performed so that the moisture content of the obtained hydrophobic boehmite nanodomain modified boron nitride is not higher than 0.15 wt%.

7. The method for preparing the high-performance multifunctional silicone sealant according to claim 1, characterized in that, In S3, based on 100 parts by weight of alkoxy-terminated polydimethylsiloxane, the hydrophobic boehmite nanodomain modified boron nitride comprises 50-90 parts by weight, spherical alumina comprises 120-220 parts by weight, dimethyl silicone oil comprises 8-18 parts by weight, and hydrophobic fumed silica comprises 1-4 parts by weight.

8. The method for preparing high-performance multifunctional silicone sealant according to claim 1, characterized in that, The vacuum dehydration mixing temperature in S3 is 100-120℃, the vacuum degree is -0.090--0.098 MPa, and the dehydration mixing time is 1-2 h; after the dehydration mixing is completed, the anhydrous base material is cooled to no higher than 40℃.

9. The method for preparing the high-performance multifunctional silicone sealant according to claim 1, characterized in that, In S4, based on 100 parts by weight of alkoxy-terminated polydimethylsiloxane, the alkoxysilane crosslinking agent includes 3-6 parts by weight of methyltrimethoxysilane and 1-3 parts by weight of vinyltrimethoxysilane; the silane coupling agent is γ-glycidoxypropyltrimethoxysilane, added in an amount of 0.5-1.5 parts by weight; and the organotitanium catalyst is diisopropyl bis(ethyl acetoacetate) titanate, added in an amount of 0.2-0.8 parts by weight.

10. A high-performance, multifunctional silicone sealant, characterized in that, The high-performance multifunctional silicone sealant is prepared by any one of claims 1 to 9. The silicone sealant is a single-component de-alcoholized room temperature vulcanizing silicone sealant, wherein the surface of the hexagonal boron nitride is distributed with discontinuous boehmite nanodomains that have been surface-treated with octyltriethoxysilane.